Combing pre-workshop, web-based learning and hands-on workshop as a flipped classroom clinical skill training model during the COVID-19 pandemic - Ting-Xuan Huang; Hsin-Hong Kuo; Tsia-Shu Lo; Ching-Chung Liang; Yi-Hao Lin; Hung-Hsueh Chou (Elsevier, 2022)
Objective: Due to the COVID-19 pandemic, there is a dramatic drop in in-person residency training due to the implementation of isolation and triage measurements. Here, we propose a new flipped classroom clinical skill training model utilizing a combination of pre-workshop, web-based learning and hands-on workshop that shortens in-person contact time to maintain residency training during the pandemic. Effectiveness of this training model was evaluated with a pre-test and post-test skills competency assessment, two-way feedback, and a five-point Likert scale structured survey questionnaire. Materials and methods: The workshop was conducted in a flipped classroom fashion by the obstetrics and gynecology (OBGYN) department of a single tertiary teaching medical center covering topics from five OBGYN subspecialities. Every topic consisted of a pre-workshop, web-based, mini lecture (PWML) followed by a hands-on workshop (HW). All first to fourth year OBGYN residents were invited to attend the workshop. All the trainees were required to complete the PWML prior to the day of HW. The workshop consisted of rotational station for each topic and was conducted within one afternoon. A 0-100-point scale pre-test and post-test skills competency evaluation were performed for each station and was assessed by the attending doctor or fellow doctor of each subspeciality. Two-way feedback was done after the post-test evaluation. A five-point Likert scale structured survey instrument consisting of participant's perceptions of the workshop design, relevance to clinical practice, and quality of instructors and materials was created during the curriculum development process and sent to each participant one month after the workshop. Results: A total of 19 residents including five first-year, six second-year, three third-year, and five fourth-year residents completed the entire pre-workshop lecture, workshop, pre-test, and post-test. For all residents, the average post-test score of 5 stations was 95 and was significantly higher than the pre-test score of 60 (p < 0.001). For both junior residents and senior residents, the average post-test scores of 5 stations were also significantly higher than pre-test scores (p < 0.001). Survey generated one month after the workshop showed a high overall satisfaction with the workshop instructors on their professional knowledge, communication skills, and interactions between the instructors and trainees. The average satisfaction scores for manipulation of vaginal breech delivery (VBD), semen analysis (SA), cervical conization (CC), obstetrics anal sphincter injury (OASIS), and laparoscopic suture techniques (LST) were 4.84, 4.96, 4.92, 4.88, and 4.92, respectively The average score for practical application of the training materials, class design and teaching method, overall satisfaction of the session, and time scheduling was 4.84, 4.96, 4.96, and 4.48, respectively. The entire HW was completed within 180 min and was carried out within half a day. Conclusion: With the implementation of isolation and triage measures in the COVID-19 pandemic, there is a dramatic drop in in-person exposure to all aspects of the residency training, in particular, non-emergent surgeries. Utilization of PWML saved 1/3 of in-person time and the entire workshop was completed within 180 min that could be carried out within half a day. The decrease of person-to-person contact time during the COVID-19 pandemic is necessary while still providing curriculum-based residency training in spite of decreased hands-on experience.